Enterprise information systems : 19th International Conference, ICEIS 2017, Porto, Portugal, April 26-29, 2017, Revised selected papers /: 19th International Conference, ICEIS 2017, Porto, Portugal, April 26-29, 2017, Revised selected papers. (2018) - Unknown
No abstract available